1989
DOI: 10.1007/bf01658433
|View full text |Cite
|
Sign up to set email alerts
|

Survival after vagotomy: Results of the Aarhus county vagotomy trial

Abstract: In order to investigate whether the previously found excess mortality in surgically-treated patients with peptic ulcer might be due partly to the resections employed, a survival analysis was undertaken in 824 patients 8-13 years after different types of vagotomy. These patients had been submitted to selective gastric vagotomy with drainage, selective gastric vagotomy with antrectomy or parietal cell vagotomy with or without drainage for duodenal ulcer, pyloric ulcer, prepyloric ulcer, or combined ulceration du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

1995
1995
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 10 publications
1
1
1
Order By: Relevance
“…However, poorer survival in ulcer perforation survivors seem to be related to excess mortality due to smoking-related disorders (C. Svanes, unpublished data). Similar findings have been reported for subjects who survived a bleeding ulcer [61] and for patients treated with elective ulcer surgery [62][63][64].…”
Section: Prognosissupporting
confidence: 84%
“…However, poorer survival in ulcer perforation survivors seem to be related to excess mortality due to smoking-related disorders (C. Svanes, unpublished data). Similar findings have been reported for subjects who survived a bleeding ulcer [61] and for patients treated with elective ulcer surgery [62][63][64].…”
Section: Prognosissupporting
confidence: 84%
“…This is in contrast with previous reported smaller studies, which showed an up to 3.3-fold death risk from gastric cancer [66,73,[92][93][94]. However, most of these patients were probably operated for duodenal ulcer disease associated with a decreased risk of stomach cancer.…”
Section: Vagotomycontrasting
confidence: 80%
“…A population-based Swedish study of 7198 vagotomized patients followed for 9 to 18 years showed a standardized incidence ratio of 1.33 (95% CI 0.92-1.86) [91]. This is in contrast with previous reported smaller studies, which showed an up to 3.3-fold death risk from gastric cancer [66,73,[92][93][94]. However, most of these patients were probably operated for duodenal ulcer disease associated with a decreased risk of stomach cancer.…”
Section: Vagotomymentioning
confidence: 74%